DAYA TERIMA DAN KANDUNGAN FLAVONOID SIRUP KOMBINASI BELIMBING WULUH (AVERRHOA BILIMBI L) DAN DAUN TIN (FICUS CARICA L) SEBAGAI MINUMAN ALTERNATIF ANTIOKSIDAN KAYA FLAVONOID[Level of Acceptance and Flavonoid Content of Syrup Made of Averrhoa bilimbi L and Ficus carica L as an Alternative Antioxidants Drinks Rich in Flavonoid] - Vetty Silvana Maulida; Annis Catur Adi (Media Gizi Indonesia, 2018)
Averrhoa bilimbi L and Ficus carica L contain many active compounds particularly fl avonoid in all parts of the plant especially its fruits and leaves. Flavonoid can be used as exogenous antioxidants. This research was done to analyze the acceptance and fl avonoid content of the formulated syrup of Averrhoa bilimbi L and Ficus carica Leaves. This research was an experimental study with completely randomized design. There were 4 times repetition in 4 formulas, one control formula (F0) and 3 modifi ed formulas (F1, F2, F3). Data was analyzed by Friedman and Wilcoxon Test (α=0.05). The result of sensory evaluation showed that the syrup was generally accepted and liked by the panelists (colour, fl avour, texture, and taste). The taste of the formula 1 (FI) was more acceptable than others. Statistical analysis showed that there was no signifi cant on differences colour between formulas. Meanwhile fl avors, texture and taste between formulas (α0.05). Syrup made of Averrhoa bilimbi L and Ficus carica L leaves are recommend as a functional food with fl avonoid content of 0.233% per 100 ml syrup or 233 mg. This fl avonoid content which can fulfi ll the fl avonoid requirement in either healthy condition or hypercholestrolemia.